2005
DOI: 10.1093/pcp/pci118
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid Accumulation Under O3 Exposure is Regulated by Ethylene in Tobacco Plants

Abstract: Ozone (O3), a major photochemical oxidant, induces leaf injury concomitant with salicylic acid (SA) synthesis. In pathogen-infected leaves, SA is synthesized via two pathways, involving phenylalanine or isochorismate. SA biosynthesis under O3 fumigation is not well understood. When we applied 14C-labeled benzoic acid (a precursor of SA in the pathway via phenylalanine) to O3-exposed tobacco leaves, it was effectively metabolized to SA. However, the activity and mRNA level of isochorismate synthase (ICS) were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 47 publications
3
68
1
2
Order By: Relevance
“…We have suggested that in ozone-exposed tobacco, SA is synthesized via the phenylalanine pathway rather than the isochorismate pathway; we came to this conclusion from the results of experiments in which we did not observe increases in tobacco ICS activity and ICS gene expression after ozone exposure and instead observed a remarkable elevation of PAL activity and PAL gene expression (Ogawa et al 2005). However, although the increase in SA levels in TMV-infected tobacco leaves has been extensively studied (Malamy et al 1990;Malamy et al 1992;Seo et al 1995), the isochorismate pathway has so far not been reported to contribute to SA synthesis in TMV-infected tobacco.…”
mentioning
confidence: 78%
“…We have suggested that in ozone-exposed tobacco, SA is synthesized via the phenylalanine pathway rather than the isochorismate pathway; we came to this conclusion from the results of experiments in which we did not observe increases in tobacco ICS activity and ICS gene expression after ozone exposure and instead observed a remarkable elevation of PAL activity and PAL gene expression (Ogawa et al 2005). However, although the increase in SA levels in TMV-infected tobacco leaves has been extensively studied (Malamy et al 1990;Malamy et al 1992;Seo et al 1995), the isochorismate pathway has so far not been reported to contribute to SA synthesis in TMV-infected tobacco.…”
mentioning
confidence: 78%
“…A major mechanism of SA deployment is through its increased synthesis in 94 response to pathogens and abiotic stresses, such as treatments with UV-C light, high light 95 radiation, and ozone (Yalpani et al, 1994;Nawrath et al, 2002;Ogawa et al, 2005;Mateo 96 et al, 2006;Catinot et al, 2008;Garcion et al, 2008). Interestingly, the Enhanced Disease 97 Susceptibility 5 (EDS5) SA transporter in the chloroplast envelope of Arabidopsis is 98 necessary for stress-induced SA accumulation, possibly due to a regulatory coupling of SA 99 transport and synthesis (Serrano et al, 2013;Yamasaki et al, 2013).…”
Section: In Arabidopsis 83mentioning
confidence: 99%
“…In ozone-induced HR-like cell death, NO accumulation preceded accumulation of ethylene, salicylic acid (SA) and leaf injury (Rao and Davis, 2001;Ogawa et al, 2005;Tamaoki, 2008). S-nitrosylation of methionine adenyl transferase1 (MAT1), which is involved in ethylene biosynthesis, inhibits ethylene production (Lindermayr et al, 2006).…”
Section: No Signaling Underlying Plant Hr Inductionmentioning
confidence: 99%